Antidepressant-Like Effects of Cistanche tubulosa Extract on Chronic Unpredictable Stress Rats Through Restoration of Gut Microbiota Homeostasis - Li, Yang; Peng, Ying; Ma, Ping; Yang, Hanlin; Xiong, Haiyan; Wang, Mengyue; Peng, Chongsheng; Tu, Pengfei; Li, Xiaobo (Frontiers in Pharmacology, 2018)
Growing evidence shows that neuropsychiatric disorders, such as depression, are linked with gut microbiome through the gut-brain axis. Cistanches Herba is well known for the treatment of “kidney-yang” deficiency in traditional Chinese medicine (TCM), and has been used for treatment of neurodegenerative diseases in recent years. In this study, chronic unpredictable stress (CUS)-induced depression model was established to explore the impact of C. tubulosa extract (CTE) on behavioral tests, monoamine neurotransmitters and neurotrophic factors in hippocampus and colon, gut microbiota composition, and short-chain fatty acids (SCFAs) production. Moreover, correlation analysis was used to evaluate the functional relationship between altered gut microbiota, changed neurotransmitters and neurotrophins in hippocampus and colon, and disturbed concentration of SCFAs. CTE significantly improved depression-like behaviors in rats under CUS. Brain level of 5-hydroxytryptamine (5-HT) and brain-derived neurotrophic factor (BDNF) expression in CUS rats were restored by CTE. The relative abundance of gut microbiota and the concentrations of acetate and hexanoic acid could also be modulated by CTE treatment. We further showed that the application of CTE in CUS rats led to strong correlation among disrupted gut microbiota composition, hippocampus neurotransmitter levels, and production of neuroactive metabolite SCFAs. Altogether, these results identify CTE as a potential treatment for depressive symptoms by restoring homeostasis of gut microbiota for microbiota-gut-brain axis disorders, opening new avenues in the field of neuropsychopharmacology.